(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about the specific characteristics of symbols. Also, together with the analysis of the linguistic nature of the symbols, the cases of relaxation in linguistic and speech phenomena, which show the speech culture, language richness and behavior of people, and serve to ensure the diversity and effectiveness of the speech, are highlighted. At the same time, the opinions of many philosophers and scientists about the symbol as a result of studying the research works were taken as information.